Monitoring Biodiversitas Ikan Sebagai Bioindikator Kesehatan Lingkungan Di Ekosistem Sungai Belawan - Helentina Mariance Manullang; Khairul Khairul (Universitas Hasanuddin, 2020)
Fish as a wealth of biological and germplasm as well as the constituent of ecological systems on a water. One of the main issues threatening fish biodiversity is the problem of environmental pollution from the company's waste into the river. Need a study that can analyse the impact of atropogonic on the presence of fish in the concept of biodiversity. Monitoring the easiest impacts of environmental pollution is to observe the biodiversity of fish as a constituent ecosystem. Based on the known literature that fish bidiversities can be used as bioindicators to determine the level of environmental pollution. This research aims to determine the condition of fish biodiversity in the region as well as the company as environmental health monitoring efforts of Belawan River. Research is conducted in an exploratory, where fish sampling station is determined through pusposive sampling method. Fish sampling using the capture equipment: fishing rod, gill nets, stocking nets, and fish trap. Data analysis using Microsoft Excel program 2010. The results of the study gained an amount of catch-up of 151 individuals derived from a total of 22 species of fish. Biodiversity Index (H’) on Station 1 (2,46), Station 2 (2,64), and Station 3 (2,45); Uniformity index (J') on Station 1 (0,82), Station 3 (0,88), and Station 3 (0,82); Dominancy Index (C) on Station 1 (0,05), Station 2 (0,06), and Stasiun3 (0,04).